Practical aspects of the use of antisipative management in the process of ensuring the economic security of an enterprise - Andriy Shtangret; Elzara Topalova; Oleg Polovcev; Olena Chornenka; Andriy Musiyovskyi (Business: Theory and Practice, 2021)
Operating in an unstable market economy environment, enterprises can achieve success in business, provided that a system of economic security is created, focused on predicting possible changes in the internal and external environment using measures. As the speed of changes in the external environment increases, it becomes more and more difficult to predict with a sufficient degree of accuracy the nature of changes, which would allow security actors to respond to them in a timely manner and with the most rational use of available resources. Early identification of a possible change in the level of economic security of an enterprise increases the reaction time to it. However, with the increase in the frequency of possible sudden changes, the degree of their predictability decreases. This means that until the moment of obtaining information sufficient for thoughtful measures, there is a shortage of time for their implementation, which can lead to the realisation of a certain threat in the form of losses or lead to the loss of a profitable economic opportunity. The main purpose of the article is to consider the essence of weak signals, to characterise the process of identifying weak signals, to formulate methodological foundations for the use of antisipative management, to determine the differences between antisipative management and adaptive and anti-crisis management in relation to the process of ensuring the economic security of an enterprise.
Keywords: H12; G32; M10; 650; antisipative management; economic security; enterprise; expert survey; decision-making systems; anti-crisis management